Study on bioremediation of azo dyes using nutraceutical industrial spent and resultant waste as filler materials to fabricate green composites / Syed Noeman Taqui - Syed Noeman , Taqui (2019)
The ever-increasing volume of spent/waste from Nutraceutical Industries accumulating into millions of tons is a serious threat to environment. Its disposal by incineration/burning as fuel adds to the carbon foot print. Nutraceutical Industrial Spent (NIS) has no feed or fertilizer value, since it has undergone process using toxic organic solvents. The present study explores the novel concept of using NIS as biosorbent for the remediation of toxic dyes and utilizing the resultant “sludge” as filler/reinforcing material with non-biodegradable plastics to fabricate polypropylene green thermoplastic and unsaturated polyester resin composites. Fennel seed spent, coriander seed spent, and cumin seed spent have been explored for bioremediation of Congo red, Acid Blue 113, Acid Red 119 and metal-complex dye, Acid Black 52 in aqueous solutions and textile industrial effluent. By batch experiments, the operating variables like initial dye concentration, adsorbent dosage, particle size, temperature, contact time and pH were optimized. pH 2 is ideal to remove azo dyes from aqueous solutions using NIS as adsorbent with enhanced adsorption capacity. For comparison, bioremediation of Congo red dye was carried out at almost neutral pH which displayed equally interesting results. The results indicate that broad range of pH 2 to 7 can be used for remediation of bisazo dyes from aqueous solutions. The adsorption methodology was studied using nine models. Of all the adsorption studies thermodynamic analysis showed the adsorption is favorable and endothermic. The low H value indicates that the adsorption is a physical process involving weak chemical interactions like hydrogen bonds and van der Waals interactions. The kinetics revealed that the adsorption process showed pseudo second-order tendencies with the equal influence of intra-particle as well as film diffusion. The process of interaction between the adsorbent and adsorbate is physical and maximum adsorption takes place between pH of 2 and 4 and at 30oC. The SEM images showed that NIS is highly fibrous matrix with a hierarchical porous structure. By FTIR presence of cellulosic and ligno-cellulosic matter in spent was confirmed and they impart hydrophilic and hydrophobic properties. The thermoplastic composites of polypropylene using dye-adsorbed NIS as filler/reinforcing material were evaluated for physico-mechanical and tribological properties and compared with polypropylene/NIS composites. Flexural strength and flexural modulus of composites were improved by adding dye-adsorbed NIS and NIS into polypropylene matrix. The wear volume of polyprolyene/dye-adsorbed NIS composites and polypropylene/NIS composites increased with increase in sliding distance, applied load and filler loading. Increased filler composition showed adverse impact on abrasive wear. The water absorption characteristics of thermoplastic composites exhibited gradual increase in weight due to hydrophilic nature of lignocellulosic filler. The SEM of surface morphology of fractured composite revealed damage to the matrix at higher dye adsorbed-NIS content. Unsaturated polyester composites of dye adsorbed-NIS and NIS showed improved chemical resistance and dimensional stability but reduced in tensile strength by increasing the filler content. The study infers that utilization of dye adsorbed-NIS as useful industrial materials may lead to creation of more jobs, ecologically alleviating waste disposal problems and helping in ameliorating the environmental pollution.